Models of resilience of the family of children with disabilities / Modele de reziliența ale familiei copiilor cu dizabilități - HARAZ Svetlana (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This article is an analysis of models of family resilience, models developed from various perspectives and factors (biological, social, psychological, relational, etc.), over several years and scientific research. Developing resilience in families caring for children with disabilities is a topic that has been addressed primarily in terms of medical approach, family stress, stressors, and less in terms of the need to increase the family's ability to cope and to adapt to the child's disability. The presence of a child with disabilities in families is a continuous stressor, a factor that requires the family to find strategies for adaptation, to find the balance between change and stability through adaptability.An analysis of the existing resilience models of the family in which children with disabilities are cared for is also important in the context of understanding resilience as a psychosocial construct for promoting resilience development models and programs. It is necessary to understand resilience and its development in the families of children with disabilities and the urgent need to develop and implement programs to develop parental resilience from the moment of finding out the diagnosis of the child and throughout life.